The effect of cardioplegic supplementation with sildenafil on cardiac energetics in a piglet model of cardiopulmonary bypass and cardioplegic arrest with warm or cold cardioplegia - Skeffington, Katie L.; Mohamed Ahmed, Eltayeb; Rapetto, Filippo; Chanoit, Guillaume; Bond, Andrew R.; Vardeu, Antonella; Ghorbel, Mohamed T.; Suleiman, M-Saadeh; Caputo, Massimo (Frontiers in Cardiovascular Medicine, 2023)
Cardioplegic cardioprotection strategies used during paediatric open-heart surgery remain suboptimal. Sildenafil, a phosphodiesterase 5 (PDE-5) inhibitor, has been shown to be cardioprotective against ischemia/reperfusion injury in a variety of experimental models and this study therefore tested the efficacy of supplementation of cardioplegia with sildenafil in a piglet model of cardiopulmonary bypass and arrest, using both cold and warm cardioplegia protocols. Piglets were anaesthetized and placed on coronary pulmonary bypass (CPB), the aorta cross-clamped and the hearts arrested for 60 minutes with cardioplegia with or without sildenafil (10nM). Twenty minutes after removal of cross clamp (reperfusion) attempts were made to wean the pigs from CPB. Termination was carried out after 60 minutes reperfusion. Throughout the protocol blood and left ventricular tissue samples were taken for analysis of selected metabolites (using HPLC) and troponin I. In both the cold and warm cardioplegia protocols there was evidence that sildenafil supplementation resulted in faster recovery of ATP levels, improved energy charge (a measure of metabolic flux) and altered release of hypoxanthine and inosine, two purine catabolites. There was no effect on troponin release within the studied short timeframe. In conclusion, sildenafil supplementation of cardioplegia resulted in improved cardiac energetics in a translational animal model of paediatric CPB surgery.